2011
DOI: 10.1080/13573322.2011.589645
|View full text |Cite
|
Sign up to set email alerts
|

Primary physical education, coaches and continuing professional development

Abstract: Physical education (PE) in primary schools has traditionally been taught by qualified primary teachers. More recently, some teaching of PE in primary schools has been undertaken by coaches (mostly football coaches) (Sports coach UK, 2004, 2007a). These coaches hold national governing body awards, but do not hold teaching qualifications. Thus, coaches may not be adequately prepared to teach PE in curriculum time. The purpose of this study was to evaluate the perceptions of a group of community based football co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 29 publications
2
51
0
Order By: Relevance
“…While acknowledging the coaches' specific subject knowledge, personal skills and enthusiasm, they were critical of their teaching and classroom management abilities. This chimes with the wider evidence that because they possess weaker pedagogical skills (Blair & Capel, 2013;Ofsted, 2009;Smith 2013) -largely due to their lack of teaching qualifications (Blair & Capel, 2011;Pickup, 2006) -coaches tend to be profoundly limited in relation to teaching styles, behaviour management, and knowledge of both the curriculum and the children themselves (Griggs, 2008(Griggs, , 2010Smith, 2013). …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…While acknowledging the coaches' specific subject knowledge, personal skills and enthusiasm, they were critical of their teaching and classroom management abilities. This chimes with the wider evidence that because they possess weaker pedagogical skills (Blair & Capel, 2013;Ofsted, 2009;Smith 2013) -largely due to their lack of teaching qualifications (Blair & Capel, 2011;Pickup, 2006) -coaches tend to be profoundly limited in relation to teaching styles, behaviour management, and knowledge of both the curriculum and the children themselves (Griggs, 2008(Griggs, , 2010Smith, 2013). …”
Section: Discussionmentioning
confidence: 99%
“…The SSP policy was not an exception, however. Indeed, it was of a piece with a range of polices since the 1980s which have tended to conflate PE with school sport (Ward & Griggs, 2011) and, in doing so, provided a justification for the use of sports coaches who then compound the issue by prioritising the teaching of sports skills (Blair & Capel, 2011;Ofsted, 2009) while neglecting other elements of NCPE which do not cohere with traditional coaching (rather than teaching) models (Blair & Capel, 2013;Griggs, 2008).…”
Section: Setting Developments In Contextmentioning
confidence: 99%
See 2 more Smart Citations
“…More specifically, these studies report that participants found it valuable to discuss everyday issues such as assessment, liability and state standards for teaching with other teachers. Blair & Capel (2011) investigated sport coaches teaching primary PE, who participated in a PE CDP program. The authors found that the coaches developed their reflective practice throughout their participation in this program.…”
Section: Reflective Practice In Pementioning
confidence: 99%